(untitled) (Research, Society and Development, 2022)
General objective: to contribute to the legal discussion of the theme that involves the rights of trans people in Brazil, since 2004, especially regarding the importance of judicial decisions, in the protection of LGBTQIA+ rights. And, as specific objectives: a) to demonstrate the extent of the jurisprudence of the Federal Supreme Court (STF) and how it has been important for the realization of fundamental rights of the LGBTQIA+ community; b) to analyze one of the main judgments, the extraordinary appeal (RE) nº 670.422, Topic 761 of the General Repercussion, and the Direct Action of unconstitutionality (ADI) nº 4.275, in which the right of transvestigenere people to be able to change the given name and sex on their official documents. Methodology: this is a bibliographic research that seeks to update the legal literature on the subject, and analyze the current legal problems related to the fundamental rights of transvestigenere people in Brazil. Result: Important judicial decisions taken by the STF, from 2011 to 2020, are identified, having as their object the protection of LGBTQIA+ rights, from two thematic axes: the promotional and the repressive. Final considerations: the performance of the STF, as a countermajoritarian Court, was proactive, but within constitutional limits. Due to the controversial nature of these decisions, an opinion was formed in Brazil that the STF decided to be a judicial protagonist, in the realization of minority rights. Because sensitive causes of moral content are decided, such as the change of name of transvestigenere people.